Entrepreneurship education in the vocational high school of agribusiness and agrotechnology fields - Hestina Windiyati; Pardjono Pardjono (Jurnal Taman Vokasi, 2018)
This research aimed to know the pattern of entrepreneurship education in the vocational high school of agribusiness and agrotechnology fields. This research used the qualitative method with a case study approach. The technique of participants determination used snowball sampling. Research participants are teachers of entrepreneurship subjects and vocational subjects (productive) of Agribusiness and Agrotechnology expertise in SMK Negeri 1 Temanggung and SMK Negeri 1 Bawen. The data were collected through interviews, observations, and other relevant sources. The data analysis technique referred to the Interactive Model of Miles, Huberman, and Saldana which includes data collection, data condensation, data display, and conclusion. This research found a pattern of entrepreneurial education consists of four stages: input, process, output, outcome. The primary strategy of entrepreneurship education is (1) learning strategies of collaboration and integration of entrepreneurial subjects with vocational subjects, (2) entrepreneurial growth strategies in schools. Entrepreneurial education outcomes are: (1) graduates choose careers as entrepreneur directly after graduating from the school, or indirectly after working first, (2) graduates can develop and expand the market.